Human capital accumulation of rural female migrants and occupational mobility at destination area: A case study of Chonburi - Saithong, Soiboon; Ayuwat, Dusadee; Chinnasri, Oranutda (International Journal of Engineering and Technology, 2018)
Occupational mobility influences the social status of female migrants who have migrated from rural to urban areas. Occupational progression leads to social class mobility. The purpose of this research was to examine human capital accumulation and occupational mobility among female migrants in the destination area. Using qualitative methodology, in-depth interviews were conducted with 26 female migrants from the rural Northeast of Thailand to Chonburi Province and with 6 key informants between October 2015 to January 2016. The data were analyzed by analytic description. The findings indicated that the female migrants from the rural Northeast of Thailand relied on multiple ways of accumulating human capital for occupational mobility, namely: 1) learning on the job, resulting in an advancement from working as a cookâ€™s assistant, waitress, or assembly line worker (Level 1 skills) to working as a tourist guide, noodle vendor, or beauty parlor/general store operator (Level 2 skills);2) attending adult education, which led to occupational advancement from being a domestic worker (Level 1 skills) to an accountant in a private company (Level 2 skills);3) studying at a formal educational institution, which helped a domestic worker to assume a position as a clerk at a state agency (Level 2 skills);4) vocational short course training, which led in occupational advancement from being an assembly line worker to opening a sewing shop (Level 2 skills). In conclusion, the findings indicated that these female migrantâ€™s way of human capital accumulation influenced their occupational mobility, but it also depended on their personal characteristics.Â